Lessons learned from cancer prevention studies with nutrients and non‐nutritive dietary constituents. Issue 6 (9th May 2016) - Yang, Chung S.; Chen, Jayson X.; Wang, Hong; Lim, Justin
Abstract : For studying nutrients, it is important to consider the nutritional status of the population and the dose of the nutrients used. For all agents, the bioavailability, dose‐response relationship and high dose toxicity should be considered. More integration between laboratory research and human studies are needed to advance the field of cancer prevention research. Abstract : Epidemiological studies have observed the association between dietary patterns and the risk of certain types of cancer. Extensive studies have been conducted on the cancer preventive activities of constituents from food and beverages. While laboratory research has shown impressive and promising results, such promising cancer preventive activities have not been demonstrated in many human intervention trials. This article analyzes the major differences between these different types of studies and the limitations of these studies. Animal and cell line studies usually use optimal conditions in order to demonstrate the hypothesized effects, sometimes without considering the human relevance. On the other hand, some clinical trials were designed without a good understanding of the biochemical and pharmacological properties of the agents used. Lessons learned from these studies will be illustrated using vitamin E, β‐carotene and selenium as examples for nutrients, and green tea polyphenols as an example for non‐nutritive dietary constituents. From the lessons learned, we believe that more interdisciplinary collaboration and integration of laboratory and human studies would effectively advance the field of cancer prevention.